Delegation vs Cost-Reducing R&D in a Cournot Duopoly - Luca Lambertini; Gabriele Primavera (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We describe a duopoly model where stockholders assess the relative profitability of delegation versus process innovation. Delegation may not be a dominant strategy. When it is, the game is not necessarily a prisoners' dilemma. Our model yields several equilibria where at least one firm remains entrepreneurial and finds it preferable to undertake cost-reducing R&D activities. Then, we introduce the possibility of using delegation and cost-reducing R&D jointly. The use of R&D investment by entrepreneurial firms is a dominated strategy, so that firms always separate ownership from control, while they don't necessarily combine delegation with process innovation.
Keywords: 330